The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ol.2018.9294
|View full text |Cite
|
Sign up to set email alerts
|

Triple primary cancer of the head and neck, skin and prostate: A case report and literature review

Abstract: Second primary cancer (SPC) is an important prognostic factor for patients with head and neck cancer (HNC); therefore, the association between the prognosis and development of SPC has been well-reported. The use of 2-[18F]-fluoro-2-deoxy-D-glucose-positron emission tomography (FDG-PET) is valuable to examine cancer stage, evaluate treatment responses and investigate suspected relapses or metastases. In the present study, the case of a male patient who was diagnosed with three primary cancer types, including we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The emergence of second primary tumours can be explained by the field cancerization phenomenon and corresponds to an important prognostic factor in head and neck cancers (Bagan et al, 2020; Maruyama et al, 2018). In our review, we found 84 cases of new primary tumours (40% of the P‐OSCC sample), 10 of which were described as third primary tumours, 1 as a fourth primary tumour and 1 as a fifth primary tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of second primary tumours can be explained by the field cancerization phenomenon and corresponds to an important prognostic factor in head and neck cancers (Bagan et al, 2020; Maruyama et al, 2018). In our review, we found 84 cases of new primary tumours (40% of the P‐OSCC sample), 10 of which were described as third primary tumours, 1 as a fourth primary tumour and 1 as a fifth primary tumour.…”
Section: Discussionmentioning
confidence: 99%